Health and safety law 2014 - A trade union guide (London, 2014)
"This new edition of the Labour Research Department‘s annual guide to health and safety law has been updated to include all the latest legal and other developments in health and safety over the past year. It covers new regulations, HSE guidance, significant court cases and the implications of new legislation. The guide is published at a time of continued and unprecedented government hostility towards health and safety regulation. Against this background and written with union negotiators and safety reps in mind, Health and Safety Law 2014 is an essential tool for reps and full-time trade union officials to use when negotiating with employers to ensure that workers are fully protected while at work."